Prevalence of Adhesive Capsulitis Among Diabetics and Non-Diabetics with Shoulder Pain in General Population: Prevalence of Adhesive Capsulitis - Seher, Zarnab; Goher, Nayyab; Hamid, Ayesha; Latif, Umaira; Bukhari, Amna; Rafique, Hira; Fatima, Kanwal; Javed, Hafiza Rabia (Pakistan Journal of Health Sciences, 2023)
Adhesive Capsulitis (AC), also known as Frozen Shoulder is the most common complaint by the diabetic patients as compared to non-diabetics, which needs to be addressed and treated in early stages as if left untreated, it may cause pain in the shoulders, loss of mobility and reduced range of motion. Objective: To find out prevalence of frozen shoulder among diabetics and non-diabetics in general population. Methods: This observational study was conducted over three hundred participants recruited by using the observational cross convenient analytical sampling technique. Participants were recruited from four cities of Punjab including Faisalabad, Lahore, Sargodha and Hafizabad. Participants of age between 25-60 years and having shoulder pain and stiffness were included in the study while those suffering from arthritis and any other musculoskeletal or systematic disorder resulting in shoulder pain were excluded. SPADI short form was used to asses shoulder pain and resulting disability in individuals. Data were then analyzed using SPSS V22. Results: The results showed that the overall prevalence of Adhesive Capsulitis was 38% with 28.07% in males and 45.70% in female, with higher prevalence in diabetic patients 66.67% then the non-diabetics 9.33%. Conclusions: This proved that Adhesive Capsulitis is proportionally higher in diabetics than non-diabetics and higher in females than males.